Multiplex IgE peanut panels: a critical appraisal of assay designs and the good, the bad, and the ugly features of the applied allergen components - D. de Boer; C. J. J. Bijnens; M. C. Slot; C. M. G. Nieuwhof; J. A. P. Bons (Frontiers in Allergy)
BackgroundMultiplex allergy assays are currently well-established in allergy diagnostics. However, the different assays in terms of designs and performance are also claimed to be heterogeneous as no agreed standards and requirements are available.ObjectiveWe aimed to compare the analytical assay designs of the ISAC, ALEX, and EUROLINE peanut (Ara h) panels and the features of the applied isoallergens and variants to create more awareness of the heterogeneity of multiplex allergy assays.MethodsWe conducted a multi-source survey in publicly available data sources and among manufacturers and performed correlation studies using patients’ serum samples.ResultsThe survey proved that the panels are indeed very heterogeneous in many ways, especially regarding the allergen component origin and isoallergen composition. Despite that, we found adequate correlations between IgE against the clinically relevant Ara h storage proteins measured by the panels. However, for the clinically relevant lipid transfer protein Ara h 9, the correlations were less adequate, which could be caused by the different Ara h 9 isoallergens used in the studied panels. For cross-reactive carbohydrate determinants (CCDs), the results were complicated, which also corresponds to the complex nature of CCDs and the different inhibition procedures. The detection of subpopulations of patients for all panallergens illustrated the heterogeneous nature of peanut IgE in general and of the peanut panels studied. Regarding the overall features provided for the three panels, we classified the peanut allergen components and CCDs by their good, bad, and even ugly features when used within these panels.ConclusionsKnowledge of the origin and respective isoallergen specifications of the peanut allergen components including the exact CCD composition is essential. Together with that of the variants, this should be documented more adequately in scientific studies and in the respective instructions for the use of multiplex allergy assays.